Strong Regionality and Dominance of Anaerobic Bacterial Taxa Characterize Diazotrophic Bacterial Communities of the Arcto-Alpine Plant Species Oxyria digyna and Saxifraga oppositifolia - Kumar, Manoj; van Elsas, Jan Dirk; Nissinen, Riitta (Frontiers in Microbiology, 2017)
Arctic and alpine biomes are most often strongly nitrogen-limited, and hence biological nitrogen fixation is a strong driver of these ecosystems. Both biomes are characterized by low temperatures and short growing seasons, but they differ in seasonality of solar radiation and in soil water balance due to underlying permafrost in the Arctic. Arcto-alpine plant species are well adapted to the low temperatures that prevail in their habitats, and plant growth is mainly limited by the availability of nutrients, in particular nitrogen, due to slow mineralization. In this study, we characterize the potential nitrogen fixing bacterial (PNFB) communities associated with two arcto-alpine pioneer plant species, Oxyria digyna (mountain sorrel) and Saxifraga oppositifolia (blue saxifrage), in three climate regions. Both of these plants readily colonize low nutrient mineral soils. Our goal was to investigate how climate (region) and, on the other hand, host plant and plant species shape these communities. Replicate samples were taken from two arctic regions, Kilpisjärvi and Ny-Ålesund, and one alpine region, Mayrhofen. In these, the PNFB communities in the bulk and rhizosphere soils and the plant endospheres were characterized by nifH-targeted PCR and massive parallel sequencing. The data revealed strong effects of region on the nitrogen fixers. Specifically, nifH sequences related to Geobacter (δ-Proteobacteria) dominated the nitrogen-fixing communities in the Mayrhofen and Kilpisjärvi regions, while members of the Clostridiales prevailed in the Kilpisjärvi and Ny-Ålesund regions. Overall, anaerobic bacterial taxa dominated the PNFB communities of the endospheres and rhizospheres of the two plant species in all study sites, especially in the High Arctic, indicating anoxic conditions created by melting snow and underlying permafrost in the arctic soils at the time of sampling (early growth season). Plant and soil communities in the Arctic were highly divergent. For example, Clostridia spp. were detected mainly in the endosphere. Interestingly, the major PNFB genera identified in this study have been previously identified as members of conserved core microbiomes in the endospheres and seeds of these plants by 16S rRNA gene based analyses combined with bacterial isolation, suggesting a very tight interaction between diazotrophic bacteria and these arctic pioneer plants.